THU0047 THE SYNOVIUM REWIRES AN IMMUNOLOGICAL RHEOSTAT THAT DEFINES TWO FUNCTIONALLY DISPARATE PATHOGENIC CD4+HLA-DR+ SUBSETS IN HUMAN ARTHRITIS. (13th June 2020) - Leong, J. Y.; Kumar, P.; Mijnheer, G.; Chen, P.; Yeo, J. G.; Tay, S. H.; Chua, C.; Hazirah, S. N.; Lai, L.; Consolaro, A.; Gattorno, M.; Arkachaisri, T.; et al.
Abstract : Background: Despite advances in understanding how the adaptive T cell landscape is affected in human arthritis, specific T cell subset knowledge has yet to be utilised in clinical settings. We have previously discovered within active arthritic patients, a circulating pathogenic-like lymphocyte (CPLs; CD4+HLA-DR+) within the T-effector compartment, that is phenotypically similar to their synovial counterparts. CPLs are inflammatory, correlate with disease activity and overlap in synovial TCR repertoire. A similar inflammation-associated T-regulatory (iaTreg; CD4+HLA-DR+) subset, that is activated, poised to migrate to inflamed site and sharing synovial TCR overlap, suggest a common disease ontogeny that may exist between CPLs and iaTregs. Objectives: Here we seek to determine whether and how the synovial microenvironment plays a role in modulating these two functionally divergent (Teff/Treg compartments) yet pathogenically homologous subsets. This modulation, akin to an immunological rheostat, may be a feature of the disease process. Methods: We examined CD45+ immune cells from synovial and PBMCs (active JIA, inactive JIA, paediatric healthy) through mass cytometry (CyToF). CD4 T cells were sorted into CPLs, iaTregs, Teff and Treg through FACS Aria II, from active JIA PBMCs, paired JIA SFMCs and healthy paediatric PBMCs and examined through ngRNASEQ. Results: Mass cytometric analysis reveal a significant enrichment of synovium signatures in both circulatory CPLs and iaTregs subsets from active arthritic PBMCs, as compared with the conventional pool of Teff/Tregs. This immunological relationship between CPLs/iaTregs is reaffirmed by comparative differential gene expression (DEG) and phylogenetic tree analysis, which indicated transcriptomic convergence between circulatory pathogenic CPLs/iaTreg subsets and divergence from their respective conventional Teff/Treg pools. Circulatory CPLs/iaTregs exhibit (a) common pathway dysregulation in T cell signalling, (b) restriction in TCR oligoclonality and (c) common transcription factor drivers within the gene regulatory network, suggesting a common pathogenic mechanism acting on these two disparate compartments. To understand how the microenvironment plays a role in modulating these two subsets, we compared the transcriptome of CPLs/iaTreg and conventional Teff/Treg subsets from (a) healthy PBMCs, (b) JIA PBMCs and (c) paired JIA SFMCs. The convergence between CPLs/iaTreg increases across the spatial/disease continuum, culminating in 7 key common dysregulated pathways within synovium CPLs/iaTregs. Importantly we detected higher clonotypic sharing of TCRs in CPLs/iaTregs across the spatial and disease continuum, suggesting a common precursor driven by antigenic selection. Conclusion: Our data suggest that CPLs/iaTregs are dichotomic components of a systemic immune rheostat, shape through the synovium environment, modulating autoimmunity in human arthritis. As iaTreg and CPL most likely have the capacity to morph into each other, the molecular crossroads which control this plasticity represent novel therapeutic targets. Disclosure of Interests: None declared